Adulet: an innovative community of practice for higher education - Chumbo, Isabel (2018)
Higher education lecturers are currently overwhelmed with the idea of changing from the old paradigm, in which teaching and learning happened through a teacher-centred perspective, to a student centred approach, currently a more widely accepted new teaching standpoint, which lecturers are eager to transform into a vivid and motivating experience, by exploring various alternatives/paths. The pressure to do so while resourcing to several technological tools is enormous. The use of technological tools available to every student, namely smartphones, social networks, new platforms and other devices do not suffice anymore. Teachers and lecturers seek to go beyond the obvious tools and search for a way to combine these technologies and the new pedagogical approach in order to provide a more profound meaning to the teaching and learning process. AduLeT – Advanced Use of Learning Technologies in higher education – is a European project involving seven different institutions, which aims at improving the teaching quality of lecturers by enhancing their skills concerning the use of technologies in an advanced way, through a Community of Practice (CoP) where methods and tools are intertwined, thus envisaging a common outcome: sharing ready-made solutions which have been tested in a higher education context to solve an educational problem.The aims of this contribution are as follows: 1. to describe the project in the given context; 2. to explain the different stages and methodology towards the design of the CoP; 3. to provide insight about the CoP itself; 4. To clarify how higher education teachers can use to CoP in their daily educational routine. The CoP is made available through a platform, currently correcting some functionalities in the evaluating stage with potential end users, which consists of an application developed with an author programming tool that allows getting flexible, visual, easy and logic navigation and interaction. The platform has been developed to provide users with a valuable experience to facilitate lecturers’ understanding and usability. Our experience shows that a CoP could facilitate the adaptation process and allow a faster and more effective transferability of teaching innovations among different countries as well as among lecturers and universities at an international level. Currently the CoP already contains methods from different fields of knowledge and a variety of tools which can allow a lecturer to choose from, in order to include them in their lectures and seminars as to obtain a better interaction from the student’s side and also to create a more motivated approach on a daily basis.